Why Fallible Human Is Superior to Technology? Technophobic Arguments in Football - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2009)
The technophobic arguments against the use of high technologies in football are being analyzed in the article. Technophobia is understood as fear of new technologies, incredibility towards them and their demonizing. Technophobic arguments are reconstructed in order to provide them (if possible) rational, non-contradictory and integral form. Therefore, the technophobic arguments are linked with the theories analyzing the impact of technology upon society. This kind of connection, on the one hand, enables better understanding of technophobes in football, and, on the other hand, makes the highlighting of shortcomings of some theories possible.